Integrasi AI dalam Pembelajaran Menulis Karya Ilmiah: Peluang dan Tantangan Orisinalitas Mahasiswa Pendidikan Bahasa dan Sastra Indonesia - Desty Endrawati Subroto; Ismail Pahmi; Ratu Bilqis Nurhaida; Devi Nurviyanti (Pusat riset dan Inovasi Nasional, 2026)
This study aims to examine the application of artificial intelligence (AI) in learning to write scientific papers and its impact on the level of originality of students in the Indonesian Language and Literature Education Study Program (PBSI) Semester VI at Bina Bangsa University. This study uses a qualitative method with a descriptive approach, which was conducted through reference searches and interviews with 30 of the total 35 students. The results of the study indicate that AI is utilized functionally as an aid in the writing process, such as compiling outlines, paraphrasing, developing ideas, and reviewing writing. Based on the interview results, the use of AI platforms is dominated by Chat GPT at 50%, followed by Perplexity at 27%, and Gemini.ai at 23%. These findings indicate that students do not rely on a single platform, but rather utilize various technologies adaptively according to their needs. In terms of discussion, the use of AI has a positive impact in the form of improved writing quality, time efficiency, development of creative ideas, increased digital literacy, and the provision of instant feedback. However, there are also challenges that arise, such as the potential for decreased originality, dependence on AI, the risk of violating academic ethics, information bias, and data privacy issues. Therefore, AI should be used as a tool, not a substitute for students' critical thinking skills. This research emphasizes the importance of using AI wisely, critically, and responsibly so that students can produce original, high-quality, and integrated scientific work in the digital age.